Implementation of an automated bathtub prototype for dogs using feedback and sequential control monitored by Labview (LACCEI, 2024)
This article describes the implementation and automation of a low-cost, domestic dog bath prototype For this, an enclosure with a wooden structure, acrylic sheets and PVC tubes was implemented, in order to provide comfort to the dog while receiving the bath. Likewise, in order to reduce the consumption of water and energy, an automation was implemented using sensors and actuators (solenoid valves, electropump and submersible resistance), a PID controller to control the water temperature, an On-Off controller to control the level of water, a sequential control for the washing and drying process, and the monitoring of the entire process through the Labview software. The PID tuning was carried out by the trial and error method where the final parameters were Kp=0.5, Ti=0.001 and Td=0.02 In addition, the establishment time to achieve the desired temperature was equal to 45.35 minutes, the time used by the sequential controller was close to 115 seconds for a given total water consumption.